Co-firing of coal with natural gas - computational simulations - Motyl, Przemysław; Łach, Jan (Advances in Mechanical and Materials Engineering)
The paper includes the results of computational tests conducted to compare coal combustion to the natural gas co-firing with coal in the combustion chamber of the conventional OP230 boiler with low-emission front burners and open-fire air (OFA) nozzles. It was shown that co-firing coal with the co-fuel with high content of methane can result in the reduction of NOx emissions about 40% compared with the coal combustion. The results obtained can be used as a benchmark for comparative computer tests of indirect co-firing of coal with syngas derived from wood- and agriculturally-based biomass and waste products.